2019
DOI: 10.1080/10942912.2019.1647234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and stability of pitaya pearls from hydrocolloids by reverse spherification

Abstract: The physicochemical properties, shelf life and stability of pitaya pearls (PP) by reverse spherification from sodium alginate (PP Alginate), kappa carrageenan (PP Kappa) and a combined iota carrageenan-sodium alginate (PP Iota) were studied. The macronutrients of PP were not affected by the hydrocolloid types, except for ash. PP Alginate showed the strongest textural properties. Storage duration affected mainly elasticity of all PP. During storage, PP Alginate and PP Kappa had better morphological and textural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
9
1
2
Order By: Relevance
“…According to the Tsai et al (2017), alginate gel gave a firm texture to LHBs due to the high affinity of G-block of alginate with Ca 2+ that results in a relatively harder LHBs. Bubin et al (2019) also recorded that hardness of red dragon fruit LHBs with alginate was 255.66 g and it was a comparatively higher value than this study.…”
Section: Texture Of Lhbscontrasting
confidence: 49%
See 1 more Smart Citation
“…According to the Tsai et al (2017), alginate gel gave a firm texture to LHBs due to the high affinity of G-block of alginate with Ca 2+ that results in a relatively harder LHBs. Bubin et al (2019) also recorded that hardness of red dragon fruit LHBs with alginate was 255.66 g and it was a comparatively higher value than this study.…”
Section: Texture Of Lhbscontrasting
confidence: 49%
“…treatments were also showed a moisture loss during storage but the reduction was not significantly different from each other (p > 0.05). Bubin et al (2019) also reported that decrement in the moisture content of LHBs made with red dragon fruit was 7.12% during 5 days of storage at 4 ± 1 C.…”
Section: Shelf Life Analysis Of Lhbsmentioning
confidence: 89%
“…Hardness indicates the stability of the beads during processing, transportation and storage (Maleki et al, 2020;Tsai et al, 2017). On the other hand, Bubin et al (2019) reported that a lower hardness, cohesiveness and rupture force with a high springiness causes the beads to burst and become chewed, portraying a chewing gum-like texture (Bubin et al, 2019). Immersion time in sugar solution was of prime importance in the peak force of the compression cycle and showed a significant positive effect.…”
Section: Resultsmentioning
confidence: 99%
“…The mango-pineapple puree was added to a plastic hemispheres mold (3 g per sphere) using a plastic dropper and was subjected to freezing at -18°C overnight. Prior to the experiment, it was transferred to a refrigerated temperature, before being left to thaw at room temperature for 30 min (Bubin et al, 2019). Sodium alginate was mixed at 0.5% (w/w) in distilled water using an ultra turrax mixer (IKA, Germany) with a speed of 800 rpm for 5 min.…”
Section: Raw Materials Preparation Processmentioning
confidence: 99%
See 1 more Smart Citation